A Low-Enriched Uranium (LEU) option for the conversion of FRM II. (April 2023) - Reiter, C.; Bergeron, A.; Bonete-Wiese, D.; Kirst, M.; Mercz, J.; Schönecker, R.; Shehu, K.; Ozar, B.; Puig, F.; Licht, J.; Petry, W.; Müller-Buschbaum, P.
Abstract: The Forschungs-Neutronenquelle Heinz Maier-Leibnitz (FRM II) is Germany's most powerful research reactor and uses Highly Enriched Uranium (HEU) fuel enriched at 93 %. The Technical University of Munich (TUM) operates the reactor and has been mandated to convert the FRM II to a lower-enrichment fuel. In preparation for the lower-enrichment fuel downselection, planned for 2023, TUM is evaluating multiple conversion scenarios. In this paper, it is demonstrated that a conversion of FRM II to Low-Enriched Uranium (LEU) is scientifically possible when using the novel monolithic U-10Mo fuel system, which is currently in the qualification process. As a research reactor, safety criteria, neutron flux distribution and cycle length are key metrics. To begin, neutronic and thermal-hydraulic models were created based on current technical drawings and relevant material properties. Specifically tailored computational methods and coupling schemes have also been developed to properly evaluate all relevant characteristics for the conversion of the FRM II reactor. Using these models and methods, a systematic parameter study was performed to explore the defined design space. The results of that study indicate that many LEU designs using monolithic U-10Mo appear to be viable to convert FRM II to LEU. One example of an LEU solution for the FRM II reactor that fulfills the stated safety, compatibility and scientific performance requirements is discussed in more detail. Highlights: An independent code-to-code comparison has proven that the neutronic and thermal-hydraulic models and methods developed for this paper can be applied to assess the relevant performance parameters of the FRM II. An extensive parameter study has shown that multiple LEU conversion designs for FRM II seem viable. A detailed study of one potential design demonstrated that a conversion of the FRM II to a fuel element using LEU fuel is scientifically possible if monolithic U-10Mo can be used in FRM II.